Effectiveness of Raw Industrial Plant Residue Amendments on Soil Chemical Properties and The Growth of Three Forage Crops - Ade Sumiahadi; Wahyudi Wahyudi; Ramazan Acar; Ahmet Tamkoc; Mehmet Hamurcu (Jurnal Ilmu Pertanian Indonesia, 2026)
Adding organic matter is required to ensure the availability and sustainability of soil organic matter. Agricultural residues constitute an important part of overall yearly biomass output and a major source of soil organic matter. The purpose of this study was to examine how five distinct industrial plant residue supplements affected soil chemical characteristics as well as the growth of three legume forage crops. The investigation was carried out over two growing seasons in the Field Crops Department's Greenhouse at Selçuk University in Turkey. The study used a Factorial RCBD design with two factors and four replications. The first factor was composed of industrial plant leftovers, which included control (soil only), wheat bran, cottonseed oilcake, sunflower seed oilcake, rapeseed oilcake, and soybean oilcake. The second factor was fodder crop species, which included forage pea, common vetch, and Narbon vetch. The results revealed that wheat bran, cottonseed oilcake, and sunflower seed oilcake increased plant growth compared to the control. Wheat bran produced the most plant growth (across all variables) in each growing season. Rapeseed and soybean oilcake additives were shown to be phytotoxic, inhibiting plant development and causing plants to yellow, wither, and die. Three plant residue amendments (wheat bran, cottonseed oilcake, and sunflower seed oilcake) improved some soil qualities. Sunflower seed oilcake-treated soils had the highest organic matter and K2O levels (1.35% and 10.33 kg/ha, respectively), whereas wheat bran-treated soils had the highest P2O5 (1.75 kg/ha). Keywords: bran, oilcakes, organic matter, seed meal